1999
DOI: 10.1080/026839699344782
|View full text |Cite
|
Sign up to set email alerts
|

Information systems prototyping in practice

Abstract: This paper describes a study of the use of prototyping approaches in information systems (IS) development. It reports a comprehensive literature review of prototyping from which we developed a taxonomy of prototyping practice. This analysis guided an empirical study which has collected data on IS practitioners' formulations of the current experience of prototyping in UK IS development organizations. These formulations are compared with data collected in a number of case studies of prototyping projects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…Any data occurs naturally by deriving it from the observation of the participants that gave no a priori significance to any particular issue. Ethnographic studies have been proven useful for empirical software engineering [8,10,32,33].…”
Section: Methodsmentioning
confidence: 99%
“…Any data occurs naturally by deriving it from the observation of the participants that gave no a priori significance to any particular issue. Ethnographic studies have been proven useful for empirical software engineering [8,10,32,33].…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the author noted that for researchers in the software engineering field, ethnographic research may provide value in the area of software development, specifically in the process of capturing tacit knowledge during the software life cycle. Later, Beynon-Davies et al [21] used ethnographic research on rapid application development to uncover the negotiated order of work in a project and the role of collective memory.…”
Section: Ethnographically-informed Studies In Software Engineeringmentioning
confidence: 99%
“…Alavi [3] studied the effectiveness of prototyping as a requirements elicitation technique by observing user and designer attitudes through field study and laboratory experiments, and provided practical suggestions for effective prototyping. In a later study, Beynon-Davies et al [16] conducted a comprehensive review on prototyping by literature survey and interviewing stakeholders from the industry.…”
Section: Requirements Identification In Rementioning
confidence: 99%
“…They reported that one-toone interview between a designer and a customer, focus group discussions, and direct 22 observations of business tasks are among the most widely used requirements elicitation techniques [201]. Prototyping is also widely used as a means of requirements elicitation [3,16]. When using this technique, a prototype is deployed and new requirements are identified as well as existing requirements are refined based on user experience and feedback.…”
Section: Requirements Identification In Rementioning
confidence: 99%